(untitled) (Aporte Santiaguino, 2023)
This compendium presents a series of methodologies relevant to investigations related to the evaluation of seismic effects in various types of bridges based on their mechanical properties, structural configurations and geometric distributions. The objective was to analyze the methodologies on seismic effects in bridges from the selected investigations. Details on the seismic behavior of specific bridge types including arch, cable-stayed and suspension bridges are presented and discussed using specific methodologies. In addition, the results of relevant studies in the field of earthquake engineering of bridges are reviewed and compared. It is concluded that these recent studies cover several advanced aspects, from seismic vulnerability assessment to the application of hysteretic methodologies in cable-stayed bridges, and new evaluation criteria such as fragility curves and improvements of design methods for suspension bridges, in addition to determining four main methodologies used in the analysis of seismic effects in bridges. Taken together, this research elements contribute to the knowledge and practice of structural and seismic engineering in bridges, providing valuable information to strengthen the safety of these structures in earthquake-prone regions.